FAKTOR PENENTU TERHADAP KEPUTUSAN PEMBELIAN PADA DUTA MODE CILACAP - Jayanti, Esih; Romadhona, Nurrizky; Zamroni, Zamroni (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to examine and analyze the effect of Product Quality (X1), Place (X2), and Promotion (X3) on Purchase Decisions (Y) at Duta Mode Cilacap. Data was collected by distributing questionnaires to 100 consumers of Duta Mode Cilacap. The sampling technique used in this study was random sampling. The data analysis techniques used include validity test, reliability test, test including linearity test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis testing including t-test and F test, coefficient analysis determination (R²). The analysis results show that product quality significantly affects purchasing decisions at Duta Mode Cilacap. Place significantly affects purchasing decisions at Duta Mode Cilacap. The promotion significantly affects purchasing decisions at Duta Mode Cilacap. Product quality, place, and promotion significantly affect Duta Mode Cilacap's purchasing decisions.